دراسـة اقتصاديـة لتسـويـق التفـاح فـي السـاحل السـوري - فاروسـي عمـر (Latakia University Journal -Biological Sciences Series, 2019)
يلعب تسويق المنتجات الزراعية دورا" هاما" في تقدم المجتمعات البشرية ورقيها . فالتسويق الذي يمد المستهلك باحتياجاته من السلع والخدمات بالكمية والنوعية والشكل الذي يريده وفي الوقت والمكان المناسبين يمكّن المنتج من الحصول على الدخل الضروري لاستمرار العملية الانتاجية والانصراف الى تطوير زراعته وأساليب انتاجه بما يسهم في زيادة دخله ورفع مستوى معيشته وتحسين ظروفه الاجتماعية والاقتصادية . تؤكد معطيات الدراسة ضعف دور شركة الخضار والفاكهة في محافظتي اللاذقية وطرطوس في استيعاب الكميات المتزايدة من التفاح في الساحل السوري وتسويقها لامداد سكان المنطقة الساحلية وبقية مناطق القطر بهذه السلعة الغذائية الهامة بالكفاءة المطلوبة اذ لم تتجاوزكمية التفاح المسوق عن طريق شركة الخضار والفواكة خلال فترة الدراســة بين عامي (1999-1990) نسبة ال (9.1-6.8) % من اجمالي انتاج الساحل السـوري من التفاح في حين تم تسـويق القسم الاعظم منه عبر تجار القطاع الخاص وهو يعادل نسبة ال (90.9-93.2) %. يتضمن البحث استعراضا" للواقع الانتاجي والتسويقي للتفاح في القطر العربي السوري ودور المؤسـسات التسويقية الحكومية في الساحل السوري في هذا المجال ومن ثم استعراض لأهم المعوقات والمقترحات التي يمكن أن تسهم في تحسين تسويق التفاح . Marketing the agricultural products plays an essential role in the development and prosperity of human societies. Thus, the marketing which provides the consumer with his requirements of goods and services qualitatively and quantitatively, and the form he wants and in the suitable time and place, enables the producer to get the necessary income for continuing the productive process, and devoting himself to develop his agriculture and the means of his production so as to help in increasing his income and raising the level of his living and improving his social and economic conditions . The results of the study ensure that the General Company For Vegetables and Apples hasn,t achieved its job in both Lattakia and Tartus in the field of enclosing and marketing the increasing amounts of apples in the Syrian Coast for providing the inhabitants of the region and other parts of the country with this nutritional piece of goods, with the required efficiency, for the quantity of the marketed apples by the company of Apples and Vegetables hasn,t exceeded the rate of (6.8% - 9.1%) from the total production of apples in the Syrian Coast during the time of the study between the years (1990-1999); meanwhile, the largest part of it has been marketed through the private section with the rate of (93.2% - 90.9% ). This research includes a review to the productive and marketing state of apples and the role of marketing government establishments in the Syrian Coast in the process of marketing apples, and then to extract the most important difficulties and suggestions which may contribute in developing the marketing of apples.